Identitas Perempuan Melalui Budaya Pernikahan: Kajian Feminisme Eksistensialis Beauvoir dalam Cerpen Ganti Lapik - Aprianto, Hendra (Universitas Ahmad Dahlan, 2024)
This article examines women's identity in marriage culture through the short story Ganti Lapik (GL) by A.A. Navis—an analytical framework using Simone de Beauvoir's existentialist feminism approach. Through analyzing the narratives in literary works, this article explores how cultural norms and women's roles make the other or shape women's identities. The study limit in this research is only on a female character named Dahniar. The stages of this research use qualitative descriptive methods with reading and note-taking techniques. The result of reading and analyzing the work obtained from this research is that Dahniar's character shows a strong woman and a fighter. Dahniar became her person while living in the city. The events that Dahniar went through to reach the peak of her freedom and independent life went through a long process in the social community. Through reading and studying GL's short stories, it can provide an understanding of the struggle of a woman who struggles independently. Literary representations of cultural and women's issues are a treasure that sparks discussion among the general public. This article invites readers to interpret Beauvoir's thoughts in literary works as a means to raise awareness of feminist issues.